Equations of Coupled Conden¬sate and Non-condensate Dynamics in the Trapped Bose Gas - Shygorin, P.; Svidzynskyj, A. (Український фізичний журнал, 2010)
We constructed equations of the condensed Bose gas dynamics at nonzero temperatures on the bases of the first principles of statistical mechanics. We derived the equation of motion for the condensate wavefunction and the quantum kinetic equation for the distribution function of excited atoms. The obtained generalized Gross–Pitaevskii equation for a condensate includes the effect of collisions with thermal cloud atoms (non-condensate). The Boltzmann quantum kinetic equation for a non-condensate was obtained by means of Zubarev’s method of nonequilibrium statistical operator. Виходячи з перших принципiв статистичної механiки, побудовано рiвняння динамiки конденсованого бозе-газу при температурах, вiдмiнних вiд нуля. Зокрема, виведено рiвняння руху для хвильової функцiї конденсату та квантове кiнетичне рiвняння для функцiї розподiлу збуджених атомiв. Одержане узагальнене рiвняння Гросс–Пiтаєвського для конденсату враховує зiткнення з надконденсатними атомами. Квантове кiнетичне рiвняння Больцмана для надконденсату отримано за допомогою методу Зубарєва нерiвноважного статистичного оператора.